1997
DOI: 10.1021/jf9609901
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Properties of a Partially Purified Cowpea (Vigna unguiculata) Globulin Modified with Protein Kinase and Glycopeptidase

Abstract: The major globulin fraction in cowpea seed was partially purified by selective ammonium sulfate precipitation and gel chromatography. The partially purified protein was enzymatically phosphorylated or deglycosylated. Phosphate content increased from 5.81 μg/mg in the untreated protein to 10.55 μg/mg in the protein kinase treated protein. Fluorescence intensity and protein solubility were significantly (p ≤ 0.05) increased at pH 3−8 as a result of phosphorylation, while susceptibility to heat-induced coagulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The results of SDS-PAGE were in agreement of a previous report on KB ( Parmar et al, 2017 ) in which polypeptides of 15–91 kDa were reported for harder-to-cook and easy-to-cook grains. The most accumulated polypeptides of 47-40 kDa along with that of 57-54 kDa might ascribe to vicilins (7S-globulin) which were reported as trimeric proteins comprising identical/non-identical subunits of 50–70 kDa held together by non-covalent hydrophobic interactions ( Aluko et al, 1997 ; Vatansever et al, 2020 ). This was in corroboration of the findings of Rui et al (2011) and Shevkani et al (2015b) for KB proteins.…”
Section: Resultsmentioning
confidence: 99%
“…The results of SDS-PAGE were in agreement of a previous report on KB ( Parmar et al, 2017 ) in which polypeptides of 15–91 kDa were reported for harder-to-cook and easy-to-cook grains. The most accumulated polypeptides of 47-40 kDa along with that of 57-54 kDa might ascribe to vicilins (7S-globulin) which were reported as trimeric proteins comprising identical/non-identical subunits of 50–70 kDa held together by non-covalent hydrophobic interactions ( Aluko et al, 1997 ; Vatansever et al, 2020 ). This was in corroboration of the findings of Rui et al (2011) and Shevkani et al (2015b) for KB proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Reducing (with mercaptoethanol) and non-reducing (without mercaptoethanol) SDS-PAGE were performed on 8-25% gradient gels using the PhastSystem Separation and Control and Development Units according to the manufacturer's instructions (GE Healthcare, Montreal, PQ) as previously described (Aluko, Yada, Lencki, & Marangoni, 1997). Gels images were acquired with Labscan on ImageScanner (GE Healthcare) and the approximate molecular weights and proportions of the proteins in each lane were analysed using the ImageQuant TL software program.…”
Section: Sodium Dodecyl Sulphate Polyacrylamide Gel Electrophoresis (mentioning
confidence: 99%